2011
DOI: 10.1248/cpb.59.1409
|View full text |Cite
|
Sign up to set email alerts
|

New Cannabinoid-Like Chromane and Chromene Derivatives from Rhododendron anthopogonoides

Abstract: Two new cannabinoid-like chromane and chromene derivatives named anthopogocyclolic acid (1) and anthopogochromenic acid (2) and five related compounds (3-7) which are known as synthetic analogues of cannabinoids: cannabichromene (CBC) type, cannabicyclol (CBL) type, and cannabicitran (CBT) type, have been isolated together with geranyl orsellinic acid (8) from the Chinese medicinal plant Rhododendron anthopogonoides. Their structures were elucidated based on spectroscopic and chemical evidence. The absolute co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 12 publications
1
44
1
Order By: Relevance
“…The ability to prenylate OSA and DVA, in addition to the previously demonstrated substrate OLA, would enable the synthesis of precursors to or direct medicinal compounds. For example, 5‐geranyl‐OSA is the precursor of anthopogochromenic and anthopogocyclolic acids, which are potential anti‐inflammatory drugs (Iwata & Kitanaka, ) and 3‐farnesyl‐OSA, also called grifolic acid, has been identified as a natural antitumor compound (Zhao et al, ) and is the precursor for the HIV drug daurichromenic acid (Taura et al, ). Furthermore, 3‐geranyl‐DVA and OLA, cannabigerovarinic acid (CBGVA) and cannabigerolic acid (CBGA), respectively, are precursors for synthesizing a variety of functionalized cannabinoids with different pharmaceutical applications (Citti et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to prenylate OSA and DVA, in addition to the previously demonstrated substrate OLA, would enable the synthesis of precursors to or direct medicinal compounds. For example, 5‐geranyl‐OSA is the precursor of anthopogochromenic and anthopogocyclolic acids, which are potential anti‐inflammatory drugs (Iwata & Kitanaka, ) and 3‐farnesyl‐OSA, also called grifolic acid, has been identified as a natural antitumor compound (Zhao et al, ) and is the precursor for the HIV drug daurichromenic acid (Taura et al, ). Furthermore, 3‐geranyl‐DVA and OLA, cannabigerovarinic acid (CBGVA) and cannabigerolic acid (CBGA), respectively, are precursors for synthesizing a variety of functionalized cannabinoids with different pharmaceutical applications (Citti et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Isoprenoids (specifically C 10 geranoid alcohols) in the aqueous phase were extracted from 2 ml samples (including 50 mg/L (Iwata & Kitanaka, 2011) and 3-farnesyl-OSA, also called grifolic acid, has been identified as a natural antitumor compound (Zhao et al, 2018) and is the precursor for the HIV drug daurichromenic acid (Taura et al, 2014). Furthermore, 3-geranyl-DVA and OLA, cannabigerovarinic acid (CBGVA) and cannabigerolic acid (CBGA), respectively, are precursors for synthesizing a variety of functionalized cannabinoids with different pharmaceutical applications (Citti et al, 2018).…”
mentioning
confidence: 99%
“…[170], liverworts [171], [172], and fungi [173][175]. Falcarinol is a skin irritant found in several plants that causes contact dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…grows in Southern China and is used as expectorant and for the treatment of chronic bronchitis [11,12]. Phytochemical studies revealed that it contains the cannabinoid-like chromane and chromene derivatives anthopogocyclolic acid, anthopogochromenic acid, cannabiorcichromenic acid, and cannabiorcicyclolic acid [11,12]. Lastly, Rhododendron rubiginosum Franch.…”
Section: Illustration Of the Structural Characteristics Of Cannabinoimentioning
confidence: 99%
“…Rhododaurichromanic acid A also showed potent anti-HIV activity, with an EC 50 of 370 ng ml −1 and a therapeutic index of 92 [94]. Anthopogocyclolic acid (CBL-type), anthopogochromenic acid (CBL-type), and cannabiorcichromenic acid (CBC-type) from R. anthopogonoides inhibit histamine release and thus exhibit antiallergic effects [11,12,91].…”
Section: Cannabinoid Acidsmentioning
confidence: 99%